2004
DOI: 10.21829/abm69.2004.983
|View full text |Cite
|
Sign up to set email alerts
|

El género Heliopsis (Heliantheae; Asteraceae) en México y las alcamidas presentes en sus raíces

Abstract: -IPN Unidad Irapuato, km 9.6 Libramiento Norte, Apdo. postal 629, 36500 Irapuato, Guanajuato, México RESUMENEl género Heliopsis pertenece a la tribu Heliantheae de la familia Asteraceae. Incluye 14 especies, la mayoría endémicas a México y aún no todas totalmente definidas. Una de ellas, Heliopsis longipes, utilizada en la medicina tradicional, se ha caracterizado por el alto contenido de alcamidas en sus raíces. El estudio de tales metabolitos ha derivado en una serie de investigaciones sobre su presencia en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
10
0
6
Order By: Relevance
“…Cuando las diferencias fueron signifi cativas se utilizó el test de Tukey HSD (Honestly-Signifi cant-Difference) para explicar las diferencias entre niveles de cada factor. Todos los análisis fueron realizados con el software STATISTICA 7 (Statsoft Inc. 1984-2004.…”
Section: Materiales Y Métodosunclassified
“…Cuando las diferencias fueron signifi cativas se utilizó el test de Tukey HSD (Honestly-Signifi cant-Difference) para explicar las diferencias entre niveles de cada factor. Todos los análisis fueron realizados con el software STATISTICA 7 (Statsoft Inc. 1984-2004.…”
Section: Materiales Y Métodosunclassified
“…It has also been reported that it produces analgesia and antiinflammation in dental and oral pathologies in humans [162], suggesting the presence of compounds with analgesic and/or anti-inflammatory properties. 19) [163][164][165]. Its chemical structure contains the three regions of capsaicin (Fig.…”
Section: Affinin (Spilanthol)mentioning
confidence: 99%
“…Only three species, however, grow north of the Mexican border (García-Chávez et al, 2004) and the only coincidentally type species of the genus penetrates far north to southeastern Canadian provinces and is reliably winter-hardy in central European climatic conditions.…”
Section: Introduction To the Botanical Issue Of The Cultivated Taxonmentioning
confidence: 99%
“…The genus Heliopsis, falling in subtribe Zinniinae also including some other genera which are popular in gardens (Urbatsch et al, 2000), contains thirteen (Fisher, 1957) to fi een (García-Chávez et al, 2004) species, both perennial and annual; yet other species add Ramirez-Noya et al (2011). Only three species, however, grow north of the Mexican border (García-Chávez et al, 2004) and the only coincidentally type species of the genus penetrates far north to southeastern Canadian provinces and is reliably winter-hardy in central European climatic conditions.…”
Section: Introduction To the Botanical Issue Of The Cultivated Taxonmentioning
confidence: 99%